D04 The effects of sodium bicarbonate ingestion and sports performance in female athletes during different phases of the menstrual cycle - Insam, Hannah; Chidley, Joel (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Sodium Bicarbonate (SB) is recognised as an effective ergogenic aid for enhancing high-intensity exercise capacity and performance. However, the lack of consistency in scientific research findings involving female participants and SB, attributed to the variations in hormonal profiles during the menstrual cycle (MC), has led to a disproportionate focus on studies exclusively conducted in a male population. Purpose: The purpose of the present study is to assess the effects of SB ingestion and sports performance in female athletes during different phases of the MC. There is currently no evidence showing whether different phases of the MC would enhance exercise performance following SB ingestion. Given this gap in the literature, it yet remains unclear that if different hormonal fluctuations throughout the MC affected absorption, nutrient capacity, or exercise performance, the stimulating effect of buffering agents could be further enhanced in future research, by identifying optimal administration strategies of SB, as well as investigating if different phases of the MC impacted exercise performance, however this is still unknown. Methods: In a double-blind, randomised, placebo-controlled trial, six eumenorrheic female athletes will complete four all-out 30-second sprints on the Wattbike, each separated by a 5-minute recovery period after receiving either 0.3g/kg body mass (BM) of SB or a placebo containing plain flour in enteric coated capsules. Performance variables collected across the duration of the experimental trials are, rate of perceived exertion (RPE), peak power output (PPO), relative peak power (RPP), heart rate (HR), anaerobic capacity (AC), and fatigue index (FI). Experimental trials will be performed in each of the following two phases of a participant’s individually characterised MC: (i) the follicular phase and (ii) the luteal phase. MC phase will be determined by using a set of home ovulation strips for the whole duration of the study. In order to control any dietary variables, participants are asked to record a 24-hour food diary for the days prior to exercise testing and are encouraged to replicate identical food and fluid intake on the day prior to experimental testing to ensure a similar metabolic state. The development of this study in this area of research could greatly enhance our understanding of how the MC and the ingestion of SB may impact female athletes and performance outcomes. Furthermore, this study would provide valuable insights into the potential impact of different MC phases on athletes and help optimise their training and performance strategies.